A new species of Metaruncina (Gastropoda: Heterobranchia: Runcinida) from Vietnam with a discussion on the so-called rudimentary radula in runcinids - Chernyshev, Alexei V. (Zootaxa, 2021)
Marine heterobranch slugs of the order Runcinida comprise 61 species, most of which inhabit the Atlantic Ocean and are referred to the genus Runcina. The Runcinida of the Pacific Ocean have been much less studied to date: only 12 species, from the genera Metaruncina Baba, 1967, Rfemsia Chernyshev, 1999, Runcinida Burn, 1963, Runcinella Odhner, 1924, Pseudoilbia M. C. Miller & Rudman, 1968, and Runcina Forbes [in Forbes and Hanley], 1851, have been described from the region. Metaruncina, Rfemsia, and Runcinida are found in the Pacific Ocean only (Baba 1954, 1967; Burn 1963; Gosliner 1991; Chernyshev 1998, 1999, 2005, 2006). The genus Metaruncina, endemic from the Pacific coast of Asia, includes two species: M. setoensis (Baba, 1954) and M. nhatrangensis Chernyshev, 2005. The latter is the only runcinid described from the coastal waters of the South China Sea, where it was found in the bays of Nha Trang and Van Phong (Chernyshev 2005). During subsequent expeditions to the coastal waters of Vietnam, this species was also recorded from off Tho Chu Island (09°19’N, 103°30’E) and off Nam Du Island (09°43′ N, 104°23′ E). However, in addition to this common species, an undescribed species of Metaruncina was collected. A description of this new species is provided in the present paper. Type material was deposited at the Museum of the A.V. Zhirmunsky National Scientific Center of Marine Biology FEB RAS, Vladivostok, Russia (MIMB).